Meat species identification using DNA based molecular techniques - C T, CHANDRE GOWDA; FAIROZE, NADEEM; S, GIRISH P; KARABASANAVAR, NAGAPPA; BAGALE, SHAILESH S (The Indian Journal of Animal Sciences, 2015)
Techniques based on nucleotide sequencing and restriction fragment length polymorphism (RFLP) targeting mitochondrial (mt) cytochrome B (cyt B) gene were developed for identification of species of meat in the present study. Universal primers flanking mt cyt B gene were designed to yield a single amplicon of 450 bp size upon polymerase chain reaction (PCR) in all meat animal species. Sequencing of mt cyt B gene of cattle (Bos indicus/ Bos taurus), buffalo (Bubalus bubalis), sheep (Ovis aries), goat (Capra hircus), chicken (Gallus gallus) and pig (Sus scrofa) was carried out and resultant sequences were aligned using Basic Local Alignment Search Tool (BLAST) of National Centre for Biotechnological Information (NCBI) to establish the homogeneity and divergence in nucleotides among these species to ascertain unambiguous identification of origin of a meat species. Closely related species like cattle & buffalo; and sheep & goat could be differentiated conclusively by sequence analysis. Although nucleotide sequencing is a highly accurate technique, it is time consuming and costly. Hence, an economical, rapid and reliable RFLP method was developed. Nucleotide sequences of amplified fragments were mapped for restriction enzyme and MspI enzyme was found to possess restriction site only in cattle (198 and 252 bp) and pig (389 and 61 bp) but not in other species studied that enabled development of an RFLP technique for the identification of beef and pork simultaneously. The PCR-RFLP technique was found applicable even in the cooked and admixed meat samples.